Development, validation and reliabilty of a questionnaire to evaluate the changes on the level of physical exercises and in daily life habits due to COVID-19 pandemic social distancing - da Cunha de Sá-Caputo, Danúbia; Sonza, Anelise; Bachur, José Alexandre; Bernardo-Filho, Mario (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim: Physical inactivity is expected to happen during the COVID-19 pandemic through home quarantine measures. The aim of this study was to develop, validate and perform the reliability of the questionnaire “Physical exercise (PE) level before and during social isolation (PEF-COVID19)” to evaluate the level of PE during the social distancing due to the COVID-19 pandemic and to try to identify changes in the daily life of the individuals. Methods: This transversal study was developed to measure psychometric properties of the questionnaire PEF-COVID19. The survey was divided into 4 sections including subjects’ characterization, social isolation update and physical exercise performed, pain, anxiety and stress before and during COVID-19 pandemic. After the survey construction in Portuguese language (Brazil), the survey was transferred to an online digital platform (Google® forms). The Construct, Clarity and Relevance Validation strategy was judged by a panel of experts and the validity index (VI) were calculated. The reliability was evaluated through the test-retest interrater reliability and measured through the intraclass correlation coefficient (ICC) and Kappa coefficient (KC). Results: Twenty-five experts participated of the survey validity and 34 respondents from the target population participated of the test-retest reliability. The general average measures for VI were all above 0.84 and test-retest ICC and KC were 0.89 and 0.88, respectively. Conclusions: This survey was considered valid and reliable to be applied to the general population over 18 years-old to investigate the PE practice and psychological aspects during the social distancing due to the COVID-19 pandemic, a public health problem.